Evaluation of Seashore Paspalum Germplasm for Resistance to Dollar Spot. Issue 1 (19th October 2017) - Steketee, Clinton J.; Martinez‐Espinoza, Alfredo D.; Harris‐Shultz, Karen R.; Henry, Gerald M.; Raymer, Paul L.
Abstract : Development of seashore paspalum ( Paspalum vaginatum Swartz) cultivars that exhibit resistance to dollar spot disease (caused by Sclerotinia homoeocarpa F.T. Bennett) are needed. Seashore paspalum is a warm‐season turfgrass often utilized on golf courses and athletic fields in the southeastern United States and other warm temperate regions of the world. Dollar spot is a significant fungal disease that causes turf quality and playability issues on fine‐textured paspalum. Management of dollar spot on seashore paspalum currently relies primarily on fungicides, but resistance to fungicides has been documented, leading to a need for improved host plant resistance. Ninety P. vaginatum accessions assembled from the USDA germplasm collection, commercially available cultivars, and University of Georgia experimental lines were screened in the field after natural S. homoeocarpa infections and using an artificial inoculation procedure for their dollar spot resistance. These accessions were evaluated visually and using digital image analysis for percent disease development over time. The experiments were conducted in hopes of finding seashore paspalum germplasm with improved genetic resistance to dollar spot disease that could be used in a breeding program. In general, percent disease varied significantly among the accessions with no discrete classes, indicating that resistance to S. homoeocarpa in seashore paspalum is likely quantitative, with several genes influencing resistance or susceptibility. Several genotypes evaluated as part of this study show promise of improving host plant resistance if used in crosses with elite seashore paspalum germplasm.